MEDIA CERAMAH DAN FILM PENDEK SEBAGAI UPAYA PENCEGAHAN PENYAKIT DIARE BERDASAR TEORI HEALTH PROMOTION MODEL (HPM) - Dian L. Azizah; Yuni S. Arief; Ilya Krisnana (Universitas Airlangga, 2014)
Introduction: Diarrhea is an infectious disease that can infect people of all age, including school age children. Knowledge of diarrhea has an effect to the incidence of diarrhea. Preventive health care is the priority key to reduce the incidence of diarrhea. Lecture with short film media is one of the ways to improve knowledge and attitude of diarrhea prevention. The focus of health promotion model (HPM) is prevention disease. The aim of this study is to analyze the influence of health education using lecture with short film media toward knowledge and attitude school age children about prevention of diarrhea with HPM approach in elementary school of Gading V Surabaya.Method: This study used pre experiment design. The respondents were 33 students, chosen with purposive sampling method. Independent variable was health education lecture method with short film media while the dependent variable was knowledge and attitude in prevention of diarrhea. The data was collected by using questionnaire. Wilcoxon signed rank test is used to analyzed (= 0.05).Results: The result indicates that there was significant influence of health education using lecture with short film media toward knowledge (p = 0.000) and attitudes (p=0.000) in prevention of diarrhea in elementary school of Gading V Surabaya.Conclussion: Giving health education using lecture with short film media can improve not only knowledge but also attitudes of school-aged children about prevention diarrhea. The next research could add more in variable of perceived benefits, perceived barriers, perceived self efficacy and activity related affect to get maximum result in study with HPM approach.